Dielectric, Pyroelectric and Ferroelectric Properties of Sn2P2(SexS1-x)6 Single Crystals. Issue 1 (15th November 2021) - Zamaraite, I.; Vysochanskii, Yu.; Dziaugys, A.; Banys, J.
Abstract: Sn2 P2 (Se x S1- x )6 ( x = 0.1, 0.2 and 0.3) crystals were grown by the vapor transport technique and their dielectric, pyroelectric and ferroelectric properties in the vicinity of phase transition were evaluated. The dielectric properties of the investigated crystals show clear anomalies associated with the ferroelectric-paraelectric phase transitions in all the compositions. The spontaneous polarization behavior of Sn2 P2 (Se x S1- x )6 crystals in the vicinity of the ferroelectric-paraelectric phase transition is discussed. The knowledge about the ferroelectric responses of Sn2 P2 (Se x S1- x )6 crystals in a broad temperature range is essential for applications in the energy storage technology. The aim of this work was to investigate the dielectric, pyroelectric and ferroelectric properties of Sn2 P2 (Se x S1- x )6 with different selenium content and compare to the parent compounds Sn2 P2 S6 and Sn2 P2 Se6 .